If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -4y = -2(1y + 4) Reorder the terms: -18 + -4y = -2(4 + 1y) -18 + -4y = (4 * -2 + 1y * -2) -18 + -4y = (-8 + -2y) Solving -18 + -4y = -8 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -18 + -4y + 2y = -8 + -2y + 2y Combine like terms: -4y + 2y = -2y -18 + -2y = -8 + -2y + 2y Combine like terms: -2y + 2y = 0 -18 + -2y = -8 + 0 -18 + -2y = -8 Add '18' to each side of the equation. -18 + 18 + -2y = -8 + 18 Combine like terms: -18 + 18 = 0 0 + -2y = -8 + 18 -2y = -8 + 18 Combine like terms: -8 + 18 = 10 -2y = 10 Divide each side by '-2'. y = -5 Simplifying y = -5
| -1k-6k=10-5k | | 8y-26=-74+2y | | 4(a-7)+8=2(a-5) | | y=10x+90 | | x+17/15=-14/15 | | 8x-8y=48 | | 6m-3=-15m | | 8x+24y=16 | | 0x+0y=15 | | 6m-3=15m | | -11-6a=1a-4 | | 3/5-8(8.8) | | 8y-26=-64+2y | | 2*x^3-3*x^2-36*x+5=0 | | 2z-28=8+8z | | .07*x=84 | | 5x-12=-17 | | 11/3*-7/2*4/5-x | | 3(a-1)=-17 | | 2*x^3-2*x^2-36*x+5=0 | | 0=121p^2-100 | | m*(-4/5)=2,23 | | 4(3x+4x)-1=91 | | .5z-1=-13 | | 7-2Inx=3 | | 800x-0.55=400x+0.45 | | f(x)=9x^2+4x+9 | | 2(j-4)=10 | | 2*16+46=x | | 2*16+46= | | x^2-cx-6c^2=0 | | 5x^10-8x^7= |